Aplikasi Edukasi Keluarga Terhadap Kemampuan Keluarga Dalam Merawat Pasien dengan Isolasi Sosial di Wilayah Kerja Rumah Sakit Bhayangkara Mataram - Hadi Nor Rahmat (Journal of Nursing Perspectives, 2025)
Mental health disorders such as schizophrenia remain a major public health issue worldwide, with social isolation being one of the most frequent manifestations that negatively affects patients’ psychosocial functioning (Rhoads, 2011; Stuart, 2009). Social isolation not only reduces communication ability and social participation but also increases relapse rates if not properly managed (Wardani, 2009). Family support plays a crucial role in the continuity of care, as inadequate knowledge and negative stigma often hinder the recovery process (Hawari, 2003; Lestari, 2008). This study aimed to analyze the effectiveness of family education in improving the ability of families to care for patients with social isolation at Bhayangkara Hospital Mataram. The research employed a case study approach with one patient diagnosed with schizophrenia and exhibiting social isolation. Interventions consisted of structured family education sessions emphasizing communication training, involvement in daily activities, and gradual social interaction. Five sequential sessions were implemented focusing on psychoeducation, skills practice, and reinforcement strategies for family caregivers. The results demonstrated that after six weeks of intervention, the patient showed increased willingness to interact socially, reduced withdrawal behavior, and improved verbal communication. Concurrently, the family’s knowledge and confidence in providing care improved significantly. These findings are consistent with prior studies indicating that psychoeducational interventions reduce relapse frequency and enhance social functioning among patients with schizophrenia (Wiyati et al., 2010; Pardede & Siregar, 2016). The study underscores the critical role of nurses in empowering families through structured education, which not only facilitates patient recovery but also helps diminish stigma surrounding mental illness. It is recommended that family education programs be systematically integrated into psychiatric nursing practice to optimize outcomes for patients with social isolation and strengthen the role of families as primary caregivers.